Indocyanine Green Fluorescence Imaging in the Surgical Management of Skin Squamous Cell Carcinoma - Zhou L; Gan Y; Wu Y; Xue D; Hu J; Zhang Y; Liu Y; Ma S; Zhou J; Luo G; Peng D; Qian W (Dove Medical Press, 2023)
Ling Zhou,1,* Yu Gan,1,* Yanjun Wu,1 Dongdong Xue,1 Jianhong Hu,1 Yilan Zhang,2 Yang Liu,3 Siyuan Ma,1 Junyi Zhou,1 Gaoxing Luo,1 Daizhi Peng,1 Wei Qian1 1Institute of Burn Research, Southwest Hospital, State Key Laboratory of Trauma, Burns and Combined Injury, Army Medical University (Third Military Medical University), Chongqing, 400038, People's Republic of China; 2Department of Oral and Maxillofacial Head and Neck Surgery, Army Medical Center of PLA/Daping Hospital, Army Medical University (Third Military Medical University), Chongqing, 400042, People's Republic of China; 3Department of Urology, Urology Institute of PLA, Southwest Hospital, Army Medical University (Third Military Medical University), Chongqing, 400038, People's Republic of China*These authors contributed equally to this workCorrespondence: Daizhi Peng; Wei Qian, Email dzpengpub@126.com; weiqian87@126.comIntroduction: Indocyanine green (ICG) fluorescence imaging has been used in the resection surgery and sentinel lymph node biopsy of many tumors. The aim of the present study is to verify the feasibility and effectiveness of ICG fluorescence imaging used for guiding the biopsy and resection of skin squamous cell carcinoma (SSCC).Methods: Sixty patients were enrolled, including 18 patients of suspected SSCC and 42 patients of diagnosed SSCC on admission. The ICG fluorescence imaging-guided skin biopsy was performed preoperatively in the 18 cases of suspected SSCC. Fifty-three patients underwent ICG fluorescence imaging-guided radical excision.Results: The results showed that 138 skin tissue samples in 60 patients with preoperative or intraoperative ICG fluorescence imaging-guide biopsy were collected. For a total number of 138 biopsies, 122 specimens were squamous cell carcinoma, and the accuracy rate was 88.4%, which was significantly higher than that of the group without preoperative ICG fluorescence imaging (41/62, 66.1%, P < 0.05). Fifty-three patients underwent surgery guided with ICG fluorescence imaging. Residual fluorescent signals in 24 patients were intraoperatively found and the excision was then expanded until the signals disappeared. Follow-up to November 2022, 12 patients died, of which 5 cases died from the tumor recurrence, and the others died due to advanced ages or other reasons. The recurrence rate was 9.4%, which was not significantly different from that of the group received routine radical resection (4/35, 11.4%, P > 0.05). Moreover, sentinel lymph nodes were successfully detected under ICG fluorescence imaging in the 4 patients with suspected lymph node metastases, and the location of lymph nodes can be precisely identified.Conclusion: ICG fluorescence imaging technique can guide the pathology biopsy to improve the accuracy of pathological examination, and help to identify the boundaries of tumor tissues and sentinel lymph nodes to resect tumor radically during operation.Keywords: indocyanine green, ICG, near-infrared fluorescence imaging, skin squamous cell carcinoma, biopsy, radical resection